1988
DOI: 10.1243/pime_proc_1988_202_012_02
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Load-Sensing Hydraulic System

Abstract: The load-sensing hydraulic system is an energy saving hydraulic system which improves the efficiency of transmitting power from the pump to the load. However, its stability characteristics deteriorate critically due to the addition of the load-sensing mechanism, compared with those of the conventional system. In this pfi!per, a non-linear mathematical model of the load-sensing hydraulic system is formulated, taking into consideration the dynamics of the load-sensing pump. Based upon linearization of this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…In addition, the volumetric flow through the directional valve opening can be assessed using equation (6) Q…”
Section: Applications Discussionmentioning
confidence: 99%
“…In addition, the volumetric flow through the directional valve opening can be assessed using equation (6) Q…”
Section: Applications Discussionmentioning
confidence: 99%
“…Similarly, the common model for the displacement controller design and evaluation of the piston pump system [15][16][17][18][19] can be modeled as follows:…”
Section: Test Rigmentioning
confidence: 99%
“…They analyzed the stability of the load-sensing (LS) controlled variable displacement pump system and found that the LS systems are prone to oscillation or even unstable behavior, because the load dynamics and the pump dynamics become inherently heavily coupled through an LS mechanism [17][18][19]. Kim et al [20] used an electronic angle sensor and an acceleration sensor to measure the dynamic state of the swash plate of a modified high-bandwidth pump control system.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic valve-controlled systems have high response but low energy-efficiency. Some researches have focused on the improvement of energy-efficiency of the hydraulic-valve-controlled systems [2][3][4][5][6]. However, it is still lower than that of the hydraulic pump-controlled system [5][6].…”
Section: Introductionmentioning
confidence: 99%